2008
DOI: 10.5194/acp-8-3185-2008
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated organic species over the tropical South American rainforest

Abstract: Abstract. Airborne measurements of the halogenated trace gases methyl chloride, methyl bromide and chloroform were conducted over the Atlantic Ocean and about 1000 km of pristine tropical rainforest in • N, 51-59 • W) in October 2005. In the boundary layer (0-1.4 km), maritime air masses, advected over the forest by southeasterly trade winds, were measured at various distances from the coast. Since the organohalogens presented here have relatively long atmospheric lifetimes (0.4-1.0 years) in comparison to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 58 publications
(83 reference statements)
4
56
3
Order By: Relevance
“…Table 1 shows an overview of the various measured species and the related measurement techniques that were applied for the different instruments for the GABRIEL campaign. Further information of the measured species is reported in Stickler et al (2007), Williams et al (2007), Gebhardt et al (2008), Eerdekens et al (2009) and Martinez et al (2010). In 10 measurement flights, of 3 to 3.5 h each, the troposphere was probed in a region between 3.5 and 6 • N and between 59 and 51 • W .…”
Section: Mission Descriptionmentioning
confidence: 99%
“…Table 1 shows an overview of the various measured species and the related measurement techniques that were applied for the different instruments for the GABRIEL campaign. Further information of the measured species is reported in Stickler et al (2007), Williams et al (2007), Gebhardt et al (2008), Eerdekens et al (2009) and Martinez et al (2010). In 10 measurement flights, of 3 to 3.5 h each, the troposphere was probed in a region between 3.5 and 6 • N and between 59 and 51 • W .…”
Section: Mission Descriptionmentioning
confidence: 99%
“…Details on the airborne instrumentation for the measurements of CO 2 , H 2 O, CO, O 3 , NO, J NO 2 , H 2 O 2 , total peroxides, OH, HO 2 , HCHO, besides VOCs can be found elsewhere (Stickler et al, 2007;Martinez et al, 2008). The measurement of volatile organic compounds by the airborne proton transfer reaction mass spectrometer (PTR-MS) are described here, whereas VOCs measured with Thermo Desorption-Gas chromatography -Mass Spectrometry (TD-GCMS) and halogenated VOC canister GC-MS analysis are described by Williams et al (2007) and Gebhardt et al (2008), respectively. A second PTR-MS was sited in the forest approximately central in the measurement region (Brownsberg, Suriname) to provide 24 h ground level data for comparison with the aircraft .…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Scheeren et al (2003) have shown that a ratio of 10 ppt ppb −1 is indicative of Asian pollution over the eastern Mediterranean. Hence the higher CH 3 Cl / CO ratios observed in P1 ([CH 3 Cl / CO] P1 = 14.1 ± 2.6 ppt ppb −1 ) compared with P2 ([CH 3 Cl / CO] P2 = 8.7 ± 1.5 ppt ppb −1 ) are indicative of pollution outflow, which may have been influenced by other strong sources such as tropical vegetation (Gebhardt et al, 2008), biofuel use (Lobert et al, 1999) or the burning of agricultural residues, waste and dung (Scheeren et al, 2002).…”
Section: Air Mass Separationmentioning
confidence: 99%
“…Problems from co-collection of ozone have been recognized previously (Goldan et al, 1995) and are documented in several studies (Bates et al, 2000;Plass-Dülmer et al, 2002;Pollmann et al, 2005;Lee et al, 2006;Apel et al, 2008;Arnts, 2008;Hellen et al, 2012). The ozone interference can be either positive via artefact formation from reaction with ozone in the sampling system (e.g.…”
Section: Ozonementioning
confidence: 99%
See 1 more Smart Citation